Leaping and Lurching into the 21st Century: A Review of Réal Fillion’s The Elective Mind Fillion, R. (2021). The elective mind: Philosophy and the undergraduate degree - Borthistle, Glenn; Hunter, Darryl (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2024)
Real Fillion asks what the place of electives, particularly philosophy, are in the contemporary Canadian university. In light of current priorities placed on career training and preparation, is there such a thing as learning for it's own sake? This book review overviews Fillion's argument that the development of the elective mind is crucial to the both the individual and to society and must be maintained. The authors analyze gaps in his appraisal of the current situation according to developments in the university in the twentieth century and provides a recommendation for additional scholarship to complete his assessment.